British Dietetic Association systematic review and evidence‐based practice guidelines for the dietary management of irritable bowel syndrome in adults (2016 update). Issue 5 (8th June 2016) - McKenzie, Y. A.; Bowyer, R. K.; Leach, H.; Gulia, P.; Horobin, J.; O'Sullivan, N. A.; Pettitt, C.; Reeves, L. B.; Seamark, L.; Williams, M.; Thompson, J.; Lomer, M. C. E.; et al.
Abstract: Background: The first British Dietetic Association (BDA) guidelines for the dietary management of irritable bowel syndrome (IBS) in adults were published in 2012. Subsequently, there has been a wealth of new research. The aim of this work was to systematically review the evidence for the role of diet in the management of IBS and to update the guidelines. Methods: Twelve questions relating to diet and IBS were defined based on review of the previous guideline questions, current evidence and clinical practice. Chosen topics were on healthy eating and lifestyle (alcohol, caffeine, spicy food, elimination diets, fat and fluid intakes and dietary habits), milk and dairy, dietary fibre, fermentable carbohydrates, gluten, probiotics and elimination diets/food hypersensitivity. Data sources were CINAHL, Cochrane Register of Controlled Trials, Embase, Medline, Scopus and Web of Science up to October 2015. Studies were assessed independently in duplicate using risk of bias tools specific to each included study based on inclusion and exclusion criteria for each question. National Health and Medical Research Council grading evidence levels were used to develop evidence statements and recommendations, in accordance with Practice‐based Evidence in Nutrition Global protocol used by the BDA. Results: Eighty‐six studies were critically appraised to generate 46 evidence statements, 15 clinical recommendations and four research recommendations. The IBS dietary algorithm was simplified to first‐line (healthy eating, provided by any healthcare professional) and second‐line [low FODMAP (fermentable oligosaccharides, disaccharides, monosaccharides and polyols) to be provided by dietitian] dietary advice. Conclusions: These guidelines provide updated comprehensive evidence‐based details to achieve the successful dietary management of IBS in adults.